Inorganic water-based capillary crystalline waterproof agent as well as preparation and use methods thereof
C-S-H gel is generated by inorganic water-based permeable compositions such as lithium silicate and sodium hydroxide in crystalline waterproofing agent, and combined with nanocellulose filaments to form a strong skeleton, which solves the poor toughness and matching degree of expansion coefficient of traditional cement-based waterproofing materials. The problem of lowness significantly improves the anti-permeability and crack resistance of concrete and extends the service life of concrete.
Patent Information
- Application Number
- CN202411106696.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-17
AI Technical Summary
The existing cement-based permeable crystalline waterproof materials have poor toughness, low coefficient of expansion matching, and poor interface compatibility, resulting in cracking, holes and other phenomena during service of the waterproof materials, which in turn deteriorates the surface strength and anti-permeability of cement concrete. Shorten the service life cycle of cement concrete.
Inorganic water-based permeable crystalline waterproofing agent is used, which consists of lithium silicate, sodium hydroxide, potassium hydroxide, reaction accelerator, surfactant, film-forming agent and anti-crack fiber. It generates C-S-H gel through chemical reactions to form a space The mesh structure enhances the compactness of concrete and uses nanocellulose filaments to form a tough skeleton, penetrate deep into the cracks and repair them, forming an integral waterproof material.
It improves the mechanical strength and permeability of concrete, extends the service life of concrete, enhances the surface acid, alkali and wear resistance, and significantly improves the waterproof effect and crack resistance of concrete.
Smart Images

Figure CN119143520A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of waterproof materials for concrete, and in particular to an inorganic water-based penetrating crystalline waterproofing agent and a preparation and use method thereof. Background Art
[0002] Modern buildings mostly use reinforced concrete structures as their main body. Under the combined influence of the physical, chemical and biological effects of the surrounding environment, concrete is prone to freeze-thaw, carbonization, alkali-aggregate reaction, cracks, etc., which causes the performance of concrete to decline, and problems such as concrete honeycombs, water leakage, and steel corrosion occur. In terms of the deterioration process, all forms of concrete damage are related to water, and water is also a carrier for the migration of corrosive salts such as chlorides and sulfates. Therefore, how to do a good job of waterproofing concrete has become a key factor in ensuring the long-term durability of concrete.
[0003] The existing waterproofing method usually adds one or more layers of waterproof coatings such as epoxy resin and polyurethane on the surface of concrete. The waterproofing principle of these waterproof materials is to prevent external moisture from invading the concrete by filling the holes in the concrete. However, since these small holes are blocked, the wall is airtight. Therefore, when moisture is discharged from the pores of the concrete, it will break through the waterproof coating and cause the coating to be damaged. In addition, due to the long-term exposure of traditional waterproof materials to the natural environment, they will age, fade and peel. Therefore, the most fundamental solution is to use waterproof materials that reduce the porosity of concrete to increase the rigidity of the concrete itself.
[0004] The commonly used rigid waterproof material is cement-based penetrating crystalline waterproof material. Traditional cement-based penetrating crystalline waterproof materials have defects such as poor toughness, low expansion coefficient matching with cement concrete matrix, and poor interface compatibility, which induce cracks and holes in the waterproof material during service, thereby deteriorating the surface strength and anti-penetration performance of cement concrete, and ultimately leading to premature failure of cement concrete protection and shortening the service life cycle of cement concrete.
[0005] In view of this, the inventor conducted in-depth research on this demand, and thus the present case was produced. Summary of the invention
[0006] In view of the above technical problems, the present invention provides an inorganic water-based penetrating crystalline waterproofing agent, which has good penetrating performance and can penetrate into the interior of concrete; and contains hydrophilic penetrating crystals and hygroscopic penetrating crystals, which can prevent liquid water and gaseous water from penetrating into concrete, and can be widely used in waterproofing operations of walls, roofs, kitchens, toilets, floors, tunnels, civil air defense projects, subways, swimming pools, sewage pools, large reservoirs and other projects of new and old concrete structures. The specific technical scheme is as follows:
[0007] An inorganic water-based penetrating crystalline waterproofing agent, characterized in that it is prepared from at least the following raw materials by mass percentage: 55.2% to 75.1% lithium silicate, 2.0% to 3.6% sodium hydroxide, 0.8% to 1.6% potassium hydroxide, 0.8% to 1.6% reaction accelerator, 0.1% to 0.15% surfactant, 0.3% to 0.6% film former, 0.4% to 0.8% anti-cracking fiber, and the rest is deionized water.
[0008] Preferably, the solid content of the lithium silicate is 20% to 22%, the modulus is 4.7 to 4.9, and the viscosity of the lithium silicate is less than or equal to 25 Pa.s at 25°C.
[0009] Preferably, the effective substance content of the sodium hydroxide is greater than 99%; the effective substance content of the potassium hydroxide is greater than 90%.
[0010] Preferably, the reaction accelerator is one or both of sodium citrate and sodium aminotriacetate; the film-forming agent is one or both of sodium methyl silicate and potassium methyl silicate.
[0011] Preferably, the surfactant is one or both of sodium dodecylbenzene sulfonate and dodecyltrimethylammonium chloride.
[0012] Preferably, the anti-cracking fibers are nanocellulose fibrils, and the effective substance content of the anti-cracking fibers is greater than 99%.
[0013] The present invention also provides a method for preparing the above-mentioned inorganic water-based penetrating crystalline waterproofing agent, comprising the following steps:
[0014] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into the reaction kettle in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a first mixed solution;
[0015] Step 2, adding the anti-cracking fiber to the first mixed solution obtained in step 1 under stirring and stirring for 60 to 90 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a second mixed solution;
[0016] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them to the reactor in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a third mixed solution;
[0017] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under stirring, and stirring for 15 to 30 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a fourth mixed solution;
[0018] Step 5: adding the film-forming agent to the fourth mixed solution under stirring, and stirring for 15 to 30 minutes. After the stirring is completed, the solution is placed under room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent.
[0019] Preferably, the stirring environment in steps 1 to 5 is a stirring speed of 120 to 150 r / min.
[0020] Preferably, the interval between adding materials in step 1 and step 3 is 5 to 10 minutes.
[0021] Among them, the intermittent addition is to prevent the temperature from rising sharply, and the temperature in the reactor is maintained within the optimal reaction temperature of the reactants; the stirring rate in the stirring environment is set to 120-150r / min to allow each group in the reactor to be completely mixed and fully reacted; the added reaction accelerator can react with the calcium ions in the concrete to form a soluble complex salt, increasing the reaction probability of the lithium silicate material and the calcium ions, and the added film-forming agent can react chemically with carbon dioxide to form a protective film to prevent external corrosive ions from corroding the concrete.
[0022] Preferably, the anti-cracking fiber in step 2 is a nanocellulose fibril wet film.
[0023] Preferably, in step 2, the nanocellulose fibril wet film is prepared by laying a microporous filter membrane with a pore size of less than or equal to 0.22 μm in a sand core funnel, and then adding 0.1-0.5% of nanocellulose fibrils into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.1-0.5 mm.
[0024] The present invention also provides a method for using the above-mentioned inorganic water-based penetrating crystalline waterproofing agent, comprising the following steps:
[0025] Step 1: Clean and moisten the concrete surface;
[0026] Step 2: Evenly spray the inorganic water-based penetrating crystalline waterproofing agent on the concrete surface twice, with the interval between the two sprayings not exceeding 12 hours;
[0027] Step 3: Spray water on the concrete surface within 12 hours after spraying. After the concrete surface is dry, wipe off the excess inorganic water-based penetrating crystalline waterproofing agent.
[0028] Preferably, the amount of inorganic water-based penetrating crystalline waterproofing agent is 0.1-0.2 kg / m 2 .
[0029] Beneficial effects:
[0030] The beneficial effects produced by the technical solution of the present invention are as follows:
[0031] (1) The inorganic water-based penetrating crystalline waterproofing agent of the present invention is prepared by mixing a lithium silicate solution with appropriate additives to react with each other, and can react chemically with calcium hydroxide in the concrete structure to generate CSH gel. The dendrite-like CSH gel overlaps each other to form a spatial network structure, which can increase the density of the concrete and form an integral waterproofing material, thereby improving the mechanical strength of the concrete structure and extending the service life of the concrete. In addition, the inorganic water-based penetrating crystalline waterproofing agent of the present invention is prepared by mixing a lithium silicate solution with appropriate additives to react with each other, and can react chemically with calcium hydroxide in the concrete structure to generate CSH gel. The dendrite-like CSH gel overlaps each other to form a spatial network structure, and can increase the density of the concrete and form an integral waterproofing material, thereby improving the mechanical strength of the concrete structure and extending the service life of the concrete. In addition, the inorganic water-based penetrating crystalline waterproofing agent of the present invention is prepared by mixing a lithium silicate solution with a suitable additive to react with each other to react with each other, and can react chemically with calcium hydroxide in the concrete structure to generate CSH gel. The inorganic water-based penetrating crystalline waterproofing agent of the present invention is prepared by mixing a lithium silicate solution with a suitable additive to react with each other ...
[0032] (2) The reaction rate between lithium silicate and calcium ions can be effectively controlled by using a reaction accelerator, thereby ensuring that the waterproof material can penetrate deep into the concrete, not only repairing the surface of the concrete, but also repairing cracks in the concrete from deep inside.
[0033] (3) The film-forming agent can react chemically with carbon dioxide in the air to form a chemical film, which makes the concrete surface resistant to acid, alkali and dirt. In addition, this film can prevent surface weathering and improve surface strength, hardness and wear resistance.
[0034] (4) After the anti-cracking fiber is sprayed on the concrete surface, the nanocellulose fibrils stretch themselves and the whiskers overlap each other to form a strong skeleton. Due to its high tensile strength, it can resist external tension and can be used as an anti-cracking material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is the SEM electron microscope image of the concrete in the control group;
[0037] Figure 2 This is the SEM electron microscope image of the concrete in Example 2;
[0038] Figure 3 This is a SEM electron microscope image of the surface nanocellulose fibrils of the waterproof material in Example 2 after curing. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Therefore, the following detailed description of the embodiments of the present invention provided is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0040] In this embodiment, lithium silicate with a small lithium ion radius is mixed with additives such as sodium hydroxide and potassium hydroxide to react with calcium hydroxide in the concrete structure to generate CSH gel. The dendrite-like CSH gel overlaps each other to form a spatial network structure, which can increase the density of the concrete and form an integral waterproof material, thereby improving the mechanical strength of the concrete structure and extending the service life of the concrete. The specific embodiments are as follows:
[0041] An inorganic water-based penetrating crystalline waterproofing agent, characterized in that it is prepared from at least the following raw materials by mass percentage: 55.2% to 75.1% lithium silicate, 2.0% to 3.6% sodium hydroxide, 0.8% to 1.6% potassium hydroxide, 0.8% to 1.6% reaction accelerator, 0.1% to 0.15% surfactant, 0.3% to 0.6% film former, 0.4% to 0.8% anti-cracking fiber, and the rest is deionized water.
[0042] As a preferred embodiment, the solid content of the lithium silicate is 20% to 22%, the modulus is 4.7 to 4.9, and the viscosity of the lithium silicate is less than or equal to 25 Pa.s at 25°C.
[0043] As a preferred embodiment, the effective substance content of the sodium hydroxide is greater than 99%; the effective substance content of the potassium hydroxide is greater than 90%.
[0044] As a preferred embodiment, the reaction accelerator is one or both of sodium citrate and sodium aminotriacetate; the film-forming agent is one or both of sodium methyl silicate and potassium methyl silicate.
[0045] As a preferred embodiment, the surfactant is one or both of sodium dodecylbenzene sulfonate and dodecyltrimethylammonium chloride.
[0046] As a preferred embodiment, the anti-cracking fibers are nanocellulose fibrils, and the effective substance content of the anti-cracking fibers is greater than 99%.
[0047] The present invention also provides a method for preparing the above-mentioned inorganic water-based penetrating crystalline waterproofing agent, comprising the following steps:
[0048] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into the reaction kettle in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a first mixed solution;
[0049] Step 2, adding the anti-cracking fiber to the first mixed solution obtained in step 1 under stirring and stirring for 60 to 90 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a second mixed solution;
[0050] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them to the reactor in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a third mixed solution;
[0051] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under stirring, and stirring for 15 to 30 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a fourth mixed solution;
[0052] Step 5: adding the film-forming agent to the fourth mixed solution under stirring, and stirring for 15 to 30 minutes. After the stirring is completed, the solution is placed under room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent.
[0053] As a preferred embodiment, the stirring environment in step 1 to step 5 is a stirring speed of 120 to 150 r / min.
[0054] As a preferred embodiment, the interval between adding materials in step 1 and step 3 is 5 to 10 minutes.
[0055] Among them, the intermittent addition is to prevent the temperature from rising sharply, and the temperature in the reactor is maintained within the optimal reaction temperature of the reactants; the stirring rate in the stirring environment is set to 120-150r / min to allow each group in the reactor to be completely mixed and fully reacted; the added reaction accelerator can react with the calcium ions in the concrete to form a soluble complex salt, increasing the reaction probability of the lithium silicate material and the calcium ions, and the added film-forming agent can react chemically with carbon dioxide to form a protective film to prevent external corrosive ions from corroding the concrete.
[0056] As a preferred embodiment, the anti-cracking fiber in step 2 is a nanocellulose fibril wet film.
[0057] As a preferred embodiment, the preparation of the nanocellulose fibril wet film in step 2 is to lay a microporous filter membrane with a pore size less than or equal to 0.22 μm in a sand core funnel, and then add 0.1-0.5% of nanocellulose fibrils into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.1-0.5 mm.
[0058] The present invention also provides a method for using the above-mentioned inorganic water-based penetrating crystalline waterproofing agent, comprising the following steps:
[0059] Step 1: Clean and moisten the concrete surface;
[0060] Step 2: Evenly spray the inorganic water-based penetrating crystalline waterproofing agent on the concrete surface twice, with the interval between the two sprayings not exceeding 12 hours;
[0061] Step 3: Spray water on the concrete surface within 12 hours after spraying. After the concrete surface is dry, wipe off the excess inorganic water-based penetrating crystalline waterproofing agent.
[0062] Preferably, the amount of inorganic water-based penetrating crystalline waterproofing agent is 0.1-0.2 kg / m 2 .
[0063] The beneficial effects of the inorganic water-based penetrating crystalline waterproofing agent and its preparation process in this embodiment are further reviewed below through several groups of examples and comparative examples.
[0064] Embodiment 1:
[0065] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0066] Lithium silicate 56%, sodium hydroxide 2.0% (effective substance content 99.5%), potassium hydroxide 0.8% (effective substance content 95%), sodium citrate 1.0%, sodium dodecylbenzene sulfonate 0.1%, potassium methyl silicate 0.3%, nanocellulose fibrils 0.4% (effective substance content 99.5%), and the rest is deionized water.
[0067] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment comprises the following steps:
[0068] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them to the reactor in sequence at intervals under a stirring speed of 120 r / min, with an addition interval of 5 minutes, stirring for 15 minutes after the addition, and placing at room temperature to cool to obtain a first mixed solution after the stirring is completed;
[0069] Step 2: Lay a microporous filter membrane with a pore size of 0.18 μm in a sand core funnel with a diameter of 7.4 cm, then stir 0.1% of nanocellulose fibrils and add them into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.1 mm, add the extracted nanocellulose fibril wet film to the first mixed solution obtained in step 1 under a stirring speed of 120 r / min and stir for 60 minutes, and after stirring, place it at room temperature to cool to obtain a second mixed solution;
[0070] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them to the reactor in sequence at intervals under a stirring speed of 120 r / min, with an addition interval of 5 min, stirring for 15 min after the addition, and leaving to cool at room temperature to obtain a third mixed solution;
[0071] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under a stirring condition at a stirring speed of 120 r / min, and stirring for 15 minutes. After the stirring is completed, the mixture is placed under room temperature to cool to obtain a fourth mixed solution;
[0072] Step 5: Add the film-forming agent to the fourth mixed solution under a stirring speed of 120 r / min and stir for 15 minutes. After the stirring is completed, place it at room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent in Example 1.
[0073] Embodiment 2:
[0074] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0075] Lithium silicate 73%, sodium hydroxide 3.6% (effective substance content 99.5%), potassium hydroxide 1.6% (effective substance content 95%), sodium citrate 1.6%, sodium dodecylbenzene sulfonate 0.15%, potassium methyl silicate 0.6%, nanocellulose fibrils 0.8% (effective substance content 99.5%), and the rest is deionized water.
[0076] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment comprises the following steps:
[0077] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into the reactor in sequence at intervals under a stirring environment with a stirring speed of 150r / min, with a feeding interval of 10min, stirring for 30min after the addition, and placing at room temperature to cool to obtain a first mixed solution after the stirring is completed;
[0078] Step 2: Lay a microporous filter membrane with a pore size of 0.22 μm in a sand core funnel with a diameter of 7.4 cm, then stir 0.5% of nanocellulose fibrils and add them into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.5 mm, add the extracted nanocellulose fibril wet film to the first mixed solution obtained in step 1 under a stirring speed of 150 r / min and stir for 90 minutes, and after the stirring is completed, place it at room temperature to cool to obtain a second mixed solution;
[0079] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them into the reactor in sequence at intervals under a stirring environment with a stirring speed of 150 r / min, with an addition interval of 10 min, stirring for 30 min after the addition, and placing at room temperature to cool to obtain a third mixed solution after the stirring is completed;
[0080] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under a stirring condition at a stirring speed of 150 r / min, and stirring for 30 minutes. After the stirring is completed, the mixture is placed under room temperature to cool to obtain a fourth mixed solution;
[0081] Step 5: Add the film-forming agent to the fourth mixed solution under a stirring speed of 150 r / min and stir for 30 minutes. After the stirring is completed, place it at room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent in Example 2.
[0082] Embodiment 3:
[0083] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0084] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0085] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment comprises the following steps:
[0086] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into the reactor in sequence at intervals under a stirring environment with a stirring speed of 140r / min, with a feeding interval of 7min, stirring for 20min after the addition, and placing at room temperature to cool to obtain a first mixed solution after the stirring is completed;
[0087] Step 2: Lay a microporous filter membrane with a pore size of 0.18 μm in a sand core funnel with a diameter of 7.4 cm, then stir 0.2% of nanocellulose fibrils and add them into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.3 mm, add the extracted nanocellulose fibril wet film to the first mixed solution obtained in step 1 under a stirring speed of 140 r / min and stir for 70 minutes, and after stirring, place it at room temperature to cool to obtain a second mixed solution;
[0088] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them to the reactor in sequence at intervals under a stirring environment with a stirring speed of 140 r / min, with a feeding interval of 7 min, stirring for 20 min after the addition, and placing at room temperature to cool to obtain a third mixed solution after the stirring is completed;
[0089] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under a stirring condition at a stirring speed of 120 r / min, and stirring for 15 minutes. After the stirring is completed, the mixture is placed under room temperature to cool to obtain a fourth mixed solution;
[0090] Step 5: Add the film-forming agent to the fourth mixed solution at a stirring speed of 140 r / min and stir for 20 minutes. After stirring, place it at room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent in Example 3.
[0091] Embodiment 4:
[0092] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0093] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium aminotriacetate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0094] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0095] Embodiment 5:
[0096] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0097] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium aminotriacetate 1.3%, dodecyltrimethylammonium chloride 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0098] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0099] Embodiment 6:
[0100] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0101] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, sodium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0102] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0103] Embodiment 7:
[0104] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0105] Lithium silicate 65%, sodium hydroxide 3.6% (effective substance content 99.5%), potassium hydroxide 1.6% (effective substance content 95%), sodium citrate 0.8%, sodium dodecylbenzene sulfonate 0.11%, potassium methyl silicate 0.6%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0106] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0107] Embodiment 8:
[0108] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0109] Lithium silicate 65%, sodium hydroxide 2.0% (effective substance content 99.5%), potassium hydroxide 0.8% (effective substance content 95%), sodium citrate 1.6%, sodium dodecylbenzene sulfonate 0.15%, potassium methyl silicate 0.3%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0110] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0111] Embodiment 9:
[0112] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0113] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 0.8%, sodium dodecylbenzene sulfonate 0.15%, potassium methyl silicate 0.6%, nanocellulose fibrils 0.4% (effective substance content 99.5%), and the rest is deionized water.
[0114] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0115] Embodiment 10:
[0116] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0117] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.15%, potassium methyl silicate 0.8%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0118] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0119] Embodiment 11:
[0120] The inorganic water-based penetrating crystalline waterproofing agent in this embodiment is made of the following raw materials by mass percentage:
[0121] Lithium silicate 65%, sodium hydroxide 2.0% (effective substance content 99.5%), potassium hydroxide 1.3% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.8% (effective substance content 99.5%), and the rest is deionized water.
[0122] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0123] Comparative Example 1:
[0124] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0125] Lithium silicate 54%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0126] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0127] Comparative Example 2:
[0128] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0129] Lithium silicate 77%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0130] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0131] Comparative Example 3:
[0132] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0133] Lithium silicate 65%, sodium hydroxide 5.0% (effective substance content 99.5%), potassium hydroxide 2.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0134] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0135] Comparative Example 4:
[0136] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0137] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.8% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0138] The preparation method of the inorganic aqueous penetrating crystalline waterproofing agent in this comparative example is consistent with that in Example 3.
[0139] Comparative Example 5:
[0140] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0141] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.8%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0142] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0143] Comparative Example 6:
[0144] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0145] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.20%, potassium methyl silicate 0.8%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0146] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0147] Comparative Example 7:
[0148] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0149] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 1.0%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0150] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0151] Comparative Example 8:
[0152] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0153] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 1.0% (effective substance content 99.5%), and the rest is deionized water.
[0154] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0155] Comparative Example 9:
[0156] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0157] Lithium silicate 65%, sodium hydroxide 3% (effective substance content 99.5%), potassium hydroxide 0.7% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0158] The preparation method of the inorganic aqueous penetrating crystalline waterproofing agent in this comparative example is consistent with that in Example 3.
[0159] Comparative Example 10:
[0160] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0161] Lithium silicate 65%, sodium hydroxide 1.9% (effective substance content 99.5%), potassium hydroxide 0.7% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0162] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0163] Comparative Example 11:
[0164] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0165] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 0.6%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0166] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0167] Comparative Example 12:
[0168] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0169] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.08%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0170] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0171] Comparative Example 13:
[0172] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0173] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.2%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0174] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0175] Comparative Example 14:
[0176] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0177] Lithium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.3% (effective substance content 99.5%), and the rest is deionized water.
[0178] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0179] Comparative Example 15:
[0180] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0181] Sodium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0182] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0183] Comparative Example 16:
[0184] The inorganic water-based penetrating crystalline waterproofing agent in this comparative example is made of the following raw materials by mass percentage:
[0185] Potassium silicate 65%, sodium hydroxide 3.0% (effective substance content 99.5%), potassium hydroxide 1.0% (effective substance content 95%), sodium citrate 1.3%, sodium dodecylbenzene sulfonate 0.12%, potassium methyl silicate 0.5%, nanocellulose fibrils 0.6% (effective substance content 99.5%), and the rest is deionized water.
[0186] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this embodiment is consistent with that in Example 3.
[0187] Comparative Example 17:
[0188] The raw material composition of the inorganic water-based penetrating crystalline waterproofing agent in this comparative example is consistent with that in Example 3.
[0189] The preparation method of the inorganic water-based penetrating crystalline waterproofing agent in this comparative example comprises the following steps:
[0190] Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into a reaction kettle under a stirring environment with a stirring speed of 140r / min, stirring for 20 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a first mixed solution;
[0191] Step 2: Lay a microporous filter membrane with a pore size of 0.18 μm in a sand core funnel with a diameter of 7.4 cm, then stir 0.2% of nanocellulose fibrils and add them into the sand core funnel to extract a nanocellulose fibril wet film with a thickness of 0.3 mm, add the extracted nanocellulose fibril wet film to the first mixed solution obtained in step 1 under a stirring speed of 140 r / min and stir for 70 minutes, and after stirring, place it at room temperature to cool to obtain a second mixed solution;
[0192] Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them into the reactor under a stirring condition at a stirring speed of 140 r / min, stirring for 20 minutes after the addition is completed, and leaving them to cool at room temperature to obtain a third mixed solution;
[0193] Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under a stirring condition at a stirring speed of 120 r / min, and stirring for 15 minutes. After the stirring is completed, the mixture is placed under room temperature to cool to obtain a fourth mixed solution;
[0194] Step 5, adding the film-forming agent to the fourth mixed solution under a stirring speed of 140 r / min, and stirring for 20 minutes. After the stirring is completed, the mixture is placed at room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent in Examples 3 to 11 and each group of comparative examples.
[0195] The method for using the inorganic water-based penetrating crystalline waterproofing agent in the above-mentioned implementation and comparative examples comprises the following steps:
[0196] Step 1: Clean and moisten the concrete surface;
[0197] Step 2: Evenly spray the inorganic water-based penetrating crystalline waterproofing agent on the concrete surface, spraying twice, with an interval of 10 hours between the two sprayings;
[0198] Step three: spray water on the concrete surface 10 hours after spraying, and wipe off the excess inorganic water-based penetrating crystalline waterproofing agent after the concrete surface is dry.
[0199] The mix ratio of each component of the concrete specimen is shown in Table 1. After the specimen is formed, it needs to be cured under standard conditions for 28 days.
[0200] Table 1 Concrete mix ratio for each group
[0201]
[0202] A concrete specimen (thickness 8.0 cm) was selected, and the waterproofing agents obtained in Examples 1-10 and Comparative Examples 1-12 were added at 0.2 kg / m 2 The spraying amount of the coating was applied on the surface of the concrete specimens, and a control group without coating was set up. Then, the concrete impermeability test, chloride ion resistance test and concrete carbonization test were carried out according to the "Test Method for Long-term Performance and Durability of Ordinary Concrete" (GB / T50082-2009). The test standards are shown in Table 2.
[0203] Table 2 Concrete material performance test standards
[0204]
[0205]
[0206] The test results are shown in Table 3.
[0207] Table 3 Performance test results
[0208]
[0209]
[0210] Combined with the test results in Table 3, it can be seen from Examples 1 to 11 that within the range of the proportions of each component given in the present invention, the concrete anti-seepage grade after being coated with the inorganic water-based penetrating crystalline waterproofing agent within the range of the component proportions given in the present invention is greatly improved, the permeability coefficient is significantly reduced, and the tensile strength and corrosion resistance are improved, indicating that the inorganic water-based penetrating crystalline waterproofing agent plays a good protective role on concrete and can significantly improve the comprehensive performance of concrete. From the comparison of Example 3 with Examples 4 to 6, it can be seen that for different reaction accelerators, film-forming agents, and surfactant raw materials, within the content range of the present invention, waterproofing agents with excellent performance can be obtained. In addition, combined with the test results of comparative examples 1 to 14, it can be seen that any component in the inorganic aqueous penetrating crystalline waterproofing agent, whether less than or more than the content range given in the present application, will affect the waterproofing protection effect of the waterproofing agent on concrete; from the test results of Example 3 and Comparative Examples 15 and 16, it can be seen that the radius of lithium ions is much smaller than that of sodium ions and potassium ions, so the penetration depth of lithium silicate is large. Compared with the waterproofing agent whose raw materials are potassium silicate and sodium silicate, the waterproofing agent made of lithium silicate can enter the deeper gaps in the concrete and react chemically with the calcium hydroxide inside the concrete structure to produce The dendrite-like CSH gel is overlapped with each other to form a spatial network structure, which can increase the density of the concrete and form an integral waterproof material, thereby improving the mechanical strength of the concrete structure and extending the service life of the concrete. It can be seen from the test results of Example 3 and Comparative Example 17 that in Comparative Example 17, when the inorganic water-based penetrating crystalline waterproofing agent was prepared, no intermittent feeding was performed, so that the temperature in the reactor rose sharply and could not be maintained at the optimal reaction temperature, thereby causing an increase in side reaction products and a decrease in target products in the reactor, resulting in a large amount of raw material waste and reducing the use effect of the waterproofing agent.
[0211] contrast Figure 1 and Figure 2 The SEM electron microscopic results of the concrete surface in the control group and Example 2 show that more CSH gel is formed in the concrete after spraying the waterproof material. These newly formed CSH gels fill the pores of the concrete, play a role in compacting the concrete and improving the anti-seepage ability of the concrete. Therefore, the waterproof material prepared by the present invention has the effect of improving the anti-seepage effect of concrete.
[0212] Figure 3 The SEM measurement of the nanocellulose fibrils on the surface of concrete in Example 2 shows that the nanocellulose fibrils overlap each other to form a mesh structure, thereby improving the tensile properties of the surface of the waterproof material and improving its crack resistance. Therefore, the waterproof material prepared by the present invention has the effect of improving the tensile properties of concrete.
[0213] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An inorganic water-based penetrating crystalline waterproofing agent, characterized in that: The invention is prepared from at least the following raw materials by mass percentage: 55.2% to 75.1% lithium silicate, 2.0% to 3.6% sodium hydroxide, 0.8% to 1.6% potassium hydroxide, 0.8% to 1.6% reaction accelerator, 0.1% to 0.15% surfactant, 0.3% to 0.6% film former, 0.4% to 0.8% anti-cracking fiber, and the rest is deionized water.
2. An inorganic water-based penetrating crystalline waterproofing agent according to claim 1, characterized in that: The solid content of the lithium silicate is 20% to 22%, the modulus is 4.7 to 4.9, and the viscosity of the lithium silicate is less than or equal to 25 Pa.s at 25°C.
3. The inorganic water-based penetrating crystalline waterproofing agent according to claim 1, characterized in that: The effective substance content of the sodium hydroxide is greater than 99%; the effective substance content of the potassium hydroxide is greater than 90%.
4. The inorganic water-based penetrating crystalline waterproofing agent according to claim 1, characterized in that: The reaction accelerator is one or both of sodium citrate and sodium aminotriacetate; the film-forming agent is one or both of sodium methyl silicate and potassium methyl silicate.
5. The inorganic water-based penetrating crystalline waterproofing agent according to claim 1, characterized in that: The surfactant is one or both of sodium dodecylbenzene sulfonate and dodecyltrimethylammonium chloride.
6. The inorganic water-based penetrating crystalline waterproofing agent according to claim 1, characterized in that: The anti-cracking fibers are nanocellulose fibrils, and the effective material content of the anti-cracking fibers is greater than 99%.
7. A method for preparing the inorganic water-based penetrating crystalline waterproofing agent according to any one of claims 1 to 6, characterized in that: The steps include: Step 1, weighing the required mass of lithium silicate, sodium hydroxide, potassium hydroxide and deionized water, and adding them into the reaction kettle in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a first mixed solution; Step 2, adding the anti-cracking fiber to the first mixed solution obtained in step 1 under stirring and stirring for 60 to 90 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a second mixed solution; Step 3, weighing the required mass of the reaction accelerator and the surfactant, and adding them to the reactor in sequence and at intervals under a stirring environment, stirring for 15 to 30 minutes after the addition is completed, and leaving it to cool at room temperature after the stirring is completed to obtain a third mixed solution; Step 4, adding the second mixed solution and the third mixed solution into a reaction kettle under stirring, and stirring for 15 to 30 minutes, and after the stirring is completed, leaving it to cool under room temperature to obtain a fourth mixed solution; Step 5: adding the film-forming agent to the fourth mixed solution under stirring, and stirring for 15 to 30 minutes. After the stirring is completed, the solution is placed under room temperature to cool to obtain the inorganic aqueous penetrating crystalline waterproofing agent.
8. The method for preparing the inorganic water-based penetrating crystalline waterproofing agent according to claim 7, characterized in that: The stirring environment in step 1 to step 5 is a stirring speed of 120 to 150 r / min.
9. The method for preparing the inorganic water-based penetrating crystalline waterproofing agent according to claim 7, characterized in that: The interval between adding materials in step 1 and step 3 is 5 to 10 minutes.
10. A method for using the inorganic water-based penetrating crystalline waterproofing agent according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: Clean and moisten the concrete surface; Step 2, spraying the inorganic water-based penetrating crystalline waterproofing agent on the concrete surface multiple times and evenly, with the interval between two adjacent sprayings not exceeding 12 hours; Step 3: Spray water on the concrete surface within 12 hours after spraying. After the concrete surface is dry, wipe off the excess inorganic water-based penetrating crystalline waterproofing agent.
Citation Information
Patent Citations
Crack-resistant waterproof cement-based permeable composite repairing material and method for preparing same
CN101531497A
Lithium-based concrete sealing solidifying agent
CN102503347A
High-permeability concrete sealed waterproofing agent and preparation method thereof
CN106565278A
Water-based capillary crystalline concrete surface layer repairing and reinforcing material as well as preparation method and application thereof
CN111620715A
